PROteolysis TArgeting Chimeras (PROTACs) - Past, Present and Future - Pettersson, Mariell (Drug Discov Today Technol, 2019)
The majority of currently used therapeutics are small molecule-based and utilize occupancy-driven pharmacology as the mode of action (MOA), in which the protein function is modulated via temporary inhibition. New modalities that operate using alternative MOAs are essential for tapping into the “undruggable” proteome. The PROteolysis Targeting Chimera (PROTAC) technology provides an attractive new approach that utilizes an event-driven MOA. Small molecule-based heterobifunctional PROTACs modulate protein target levels by hijacking the ubiquitin-proteasome system to induce degradation of the target. Here, we address important milestones in the development of the PROTAC technology, as well as emphasize key findings from this previous year and highlight future directions of this promising drug discovery modality.